2021
DOI: 10.1080/1062726x.2021.1981332
|View full text |Cite
|
Sign up to set email alerts
|

The role of public relations in corporate diplomacy: how relationship cultivation increases organizational legitimacy

Abstract: Drawing from neo-institutionalism and public relations theory, this study examined to what extent corporate diplomacy builds on public relations to identify and respond to societal expectations emerging from a company's host country environment, which can result in organizational legitimacy. Based on in-depth interviews (N = 25) with public relations executives in the United Arab Emirates, our findings imply that companies engage in corporate diplomacy to align with governmental demands while simultaneously at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Most organizations engaging in public affairs in Kenya tend to be international corporations with regional headquarters in the country. This has strong links to the literature on organizational and corporate diplomacy (Marschlich and Ingenhoff, 2021). Organizations such as Google, Microsoft and IBM are examples, making Kenya, alongside Nigeria and South Africa, a leader in sub-Saharan Africa.…”
Section: Public Affairs and The Public Interestmentioning
confidence: 73%
“…Most organizations engaging in public affairs in Kenya tend to be international corporations with regional headquarters in the country. This has strong links to the literature on organizational and corporate diplomacy (Marschlich and Ingenhoff, 2021). Organizations such as Google, Microsoft and IBM are examples, making Kenya, alongside Nigeria and South Africa, a leader in sub-Saharan Africa.…”
Section: Public Affairs and The Public Interestmentioning
confidence: 73%
“…Fitzpatrick et al (2020), in their recent investigation into the corporate diplomacy practices of US.-based MNCs, concluded that foreign corporations intentionally use corporate diplomacy to build relationships with critical actors in host countries, including other corporations and host governments. Others have explored corporate perspectives on corporate diplomacy practices and found that MNCs use corporate diplomacy as a communication strategy to develop various intangible assets, including legitimacy (Marschlich and Ingenhoff, 2021). The study revealed that news media actors rank among the most important institutional actors in a host country that MNCs seek to communicate and engage with (Marschlich and Ingenhoff, 2021).…”
Section: Ccijmentioning
confidence: 97%
“…Others have explored corporate perspectives on corporate diplomacy practices and found that MNCs use corporate diplomacy as a communication strategy to develop various intangible assets, including legitimacy (Marschlich and Ingenhoff, 2021). The study revealed that news media actors rank among the most important institutional actors in a host country that MNCs seek to communicate and engage with (Marschlich and Ingenhoff, 2021). However, which role media play in influencing MNCs' legitimacy has not yet been examined, which prompted us to develop two research questions for our study: RQ1.…”
Section: Ccij 287mentioning
confidence: 99%
See 1 more Smart Citation
“…Against this background, new forms of corporate social engagement have emerged, including CSA (Dodd and Supa, 2014, 2015), corporate and chief executive officer (CEO) activism (Chatterji and Toffel, 2019), corporate diplomacy (Marschlich and Ingenhoff, 2021) and political CSR (Ingenhoff and Marschlich, 2019). The distinction between the terms is not always precise, and they are sometimes used synonymously.…”
Section: Literature Reviewmentioning
confidence: 99%